Pengaruh Storytelling Media Audio Visual Terhadap Perilaku Cuci Tangan Pakai Sabun Pada Anak Usia Prasekolah Pada Masa Pandemi Covid-19 di Raudhatul Athfal Baitul Hikmah Kota Depok - Purwati, Renny (Abdi Geomedisains, 2024)
The phenomenon found that children of pre-school age have the habit of not paying attention to the need to wash their hands and the low ability to wash their hands 6 steps in children of pre-school age. 6-step handwashing behavior is an activity carried out in cleaning hands with 6 steps aimed at maintaining cleanliness and killing germs disease. This study aims to determine the influence of storytelling with audio-visual media on the behavior of washing hands with soap in preschool-age children in Raudhatul Athfal Baitul Hikmah, Depok City. The sampling method in this study used a one-group pretest posttest design with a cross-sectional approach, a total sampling technique of 20 respondents. The results showed pretest behavior as much as 30%, and posttest behavior  by 70% there was a difference between pretest and posttest by 40% with a P Value value = 0.000 < α 0.05). So it can be concluded that storytelling with audio-visual media about the behavior of washing hands with soap in preschool-age children has a significant effect on the ability to wash hands 6 steps in preschool age children. Therefore, it is hoped that all parties will be able to apply and develop using storytelling methods (audio-visual) that have been proven effective in increasing knowledge and changing health behaviors in pre-school age.